Writing for Concentration, Intelligence, and Aesthetics in the Epidemic Situation of Coronavirus Disease 2019 - Jinphattharapornkul, Chatphon (Journal of Liberal Arts RMUTT, 2024)
The purpose of this study was to present how to write creatively or create a literary text. There are methods for studying writing according to literary traditions, including: 1) creative writing style landscaping; 2) poetry writing; 3) prose or narrative writing; and 4) novel or long narrative writing. The results of the study revealed that the COVID-19 pandemic has posed significant threats to human life and well-being, impacting both art and science. Facing this invisible catastrophe, the importance of high-quality medical equipment and vaccines is undeniable for controlling and eradicating such pathogens. Humans require mindfulness and concentration skills to harness their intellectual potential and effectively navigate crises. There are also many ways to build these three potentials. However, one way to achieve a good process and lead to a destination with minimal waste of resources and time is by writing. To create a thinking system with concentration, intelligence, and aesthetics as the basis for all systems of the body and mind, writing is used as a tool for recovery and lifestyle adaptation to be suitable and safe from the COVID-19 virus in a sustainable way.